1974
DOI: 10.1111/j.1471-0528.1974.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypophysial Hormones and Human Chorionic Gonadotrophin (Hcg) on the Anencephalic Fetal Adrenal Cortex and on Parturition in the Human

Abstract: Summary The present study examined whether the adrenal of the anencephalic fetus could be stimulated in utero with adrenocorticotrophic hormone (ACTH) or human chorionic gonadotrophin (HCG) injected directly into the fetus. The effect of the injections was judged by measuring hormone levels and by histological and histochemical examination of the fetal adrenals. The effect was also studied of stimulation of the fetal adrenal or the injection of neurohypophysial hormones on the initiation of parturition. HCG ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In sheep, the fetal hypothalamic pituitary axis plays a key role in the onset of labor by triggering the release of corticotropin [38], whereas fetal oxytocin probably does not contribute to the mechanism underlying ovine parturition. Injection of posteriorlobe hormones into human anencephalic fetuses has produced maternal uterine contractions [34]. Oxytocin can cross the primate placenta in both directions without degradation, according to DAWOOD et al [16], However, to reach the myometrial receptor sites the hormone has to be circulated in the maternal bloodstream, and this pathway is likely to lead to its inactivation [39].…”
Section: Discussionmentioning
confidence: 99%
“…In sheep, the fetal hypothalamic pituitary axis plays a key role in the onset of labor by triggering the release of corticotropin [38], whereas fetal oxytocin probably does not contribute to the mechanism underlying ovine parturition. Injection of posteriorlobe hormones into human anencephalic fetuses has produced maternal uterine contractions [34]. Oxytocin can cross the primate placenta in both directions without degradation, according to DAWOOD et al [16], However, to reach the myometrial receptor sites the hormone has to be circulated in the maternal bloodstream, and this pathway is likely to lead to its inactivation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Morphologic studies of adrenal gland development from anencephalic and apituitary human fetuses have shown normal development prior to 15 weeks of gestation but subsequent atrophy of the inner fetal zone thereafter (10). Adrenal atrophy in human anencephalic fetuses was prevented by ACTH treatment in utero (11)(12)(13). These data strongly suggest that human fetal adrenal growth, and in particular the rapid growth of the fetal zone, is dependent upon an intact pituitary and may be regulated by ACTH.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that hCG stimulates the growth of the adrenal gland of the anencephalic fetus before 20 weeks gestation (20,41,55). However, Honnebier et al (58), who injected anencephalic fetuses with hCG before delivery, observed no demonstrable increase in steroid secretion. Recently, it has been reported that the adrenals of anencephalic abortuses are smaller and have reduced amounts of fetal zone cells by as early as 15 weeks gestation (83,105).…”
Section: Adrenal Tissue Of Human Anencephalic Abortuses and Newbmentioning
confidence: 96%